Opinion of medical students and instructors on the challenges of in-person learning postcoronavirus disease 2019 pandemic - Ahmed A. Alsunni; Rabia Latif; Deena A. Aldossary; Lama I. Aloraifi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Several universities switched back to face-to-face teaching in 2022 after 2 years of online classes during the coronavirus disease 2019 (COVID-19) crisis. There is no data from these students/teachers on the challenges in postpandemic face-to-face teaching and learning. The current study's aim was to identify the challenges of face-to-face teaching and learning postpandemic from the perspective of students and instructors. MATERIALS AND METHODS: Undergraduate medical students (n = 210) registered in Imam Abdulrahman Bin Faisal University and instructors (n = 72) filled out online questionnaires from November 2022 to March 2023 on teaching-learning challenges in the postpandemic period. The questionnaires asked students about their interest in education, scores, degree of shyness, how clear the voices of the instructors wearing face masks were, fear of COVID-19, preferred mode of teaching, and advantages/disadvantages of face-to-face teaching. Descriptive statistics included frequencies and percentages for qualitative variables; Chi-square test was applied to assess association between categorical variables. RESULTS: Students reported a decrease in their educational interest postpandemic (47.1%), diffidence in interaction (42.4%), blurred teachers' voices because of the face masks (63.3%), and lack of teachers' empathy (47.6%). There was a significant association between preclinical year students and a decrease in educational interest (P = 0.002), diffidence in class interactions (P = 0.001), and fear of contracting COVID-19 infection while interacting with teachers (P = 0.04). Instructors complained of a decrease in students' interest in education (65.3%), especially the instructors of the clinical years (16.7% vs. 2.1%; P = 0.022). About 10% students reported taking leave from university on purpose due to fear of contracting COVID-19 infection; students and instructors both supported lecture recordings (98.6% and 63.9%, respectively). The students' and instructors' preferred platform for learning was "hybrid" (80.5% and 63.9%, respectively). CONCLUSION: Challenges faced by the students include decreased interest in learning, drop in scores, muffled voices because of the face masks, increased shyness, waste of time in commutes, lack of flexibility in schedules, increased workload, and fear of catching COVID-19 infection. There is strong support for hybrid/blended learning and recording lectures.